2017
DOI: 10.1093/fampra/cmx101
|View full text |Cite
|
Sign up to set email alerts
|

International exchanges in primary care—learning from thy neighbour

Abstract: This systematic review describes how international exchange programmes in primary care have been received and evaluated. Electronic databases (MEDLINE, Embase, PsycINFO, EBM reviews, CAB abstracts and PubMED) were searched to identify articles where the main focus of the study was exchanges undertaken in primary care/family medicine until March 2016. Articles were included if they (i) discussed participant exchanges in primary care; (ii) presented associated outcome data-this included (a) individual/group expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These findings echo those of other exchange schemes for established clinicians whether national or international. Such time is valuable; it can develop clinical practice ( Axon, 1998 ) and enhance appreciation of care and clinical practice in different contexts ( Bridgwood et al , 2017 ; Bridgwood et al , 2018 ; Jelley, 2002 ; Van Dormael et al , 2007 ; Van den Heuvel & Hood (2010) ; Zwart et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings echo those of other exchange schemes for established clinicians whether national or international. Such time is valuable; it can develop clinical practice ( Axon, 1998 ) and enhance appreciation of care and clinical practice in different contexts ( Bridgwood et al , 2017 ; Bridgwood et al , 2018 ; Jelley, 2002 ; Van Dormael et al , 2007 ; Van den Heuvel & Hood (2010) ; Zwart et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The value of observing colleagues in the workplace ( Bridgwood et al , 2018 ) or sharing experience of different work contexts ( Sampson et al , 2017 ; Stewart & Cunningham, 2021 ; Wedderburn et al , 2012 ) is well recognised in the healthcare workplace exchange literature as promoting insight for doctors located in other clinical contexts, improving communication across medical contexts ( Sampson et al , 2016 ), and enabling professionals to gain an appreciation of shared aspects of work including challenges and opportunities for development ( Lee et al ., 2019 ). Indeed, the value of spending time across clinical contexts is arguably growing in importance for doctors across the continuum of education due to the increasingly interconnected nature of care and appreciation of healthcare matters ( Barata & Rigon, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A review also corroborates the present findings on the need to establish partnerships to improve care. The review highlights that beneficiaries of such exchange or partnership programmes benefit both personally and professionally where skills from such collaborations are often applied to improve patients outcomes …”
Section: Discussionmentioning
confidence: 99%
“…The review highlights that beneficiaries of such exchange or partnership programmes benefit both personally and professionally where skills from such collaborations are often applied to improve patients outcomes. 27 Participants also emphasized the need for competency-based training in acute stroke care through professional development and training opportunities, particularly in areas such as diagnostic algorithms for stroke, including the use of stroke scales, and other treatment protocols. Studies in HICs underscore this as part of measures to improve stroke care.…”
Section: Discussionmentioning
confidence: 99%
“…World Organization of Family Doctors (WONCA) Global Family Doctor: www.globalfamilydoctor.com European Young Family Doctors Movement (EYFDM): https://eyfdm.eu Royal College of General Practitioners Junior International Committee (RCGP JIC): www.rcgp.org.uk/membership/ international/international-opportunities students, nurses, GP trainees, GPs and visiting scholars (Bridgwood et al, 2018). This review found evidence of multiple benefits of exchanges, including enhanced communication and consulting skills, increased understanding of resources and limitations and enhanced intercultural medical professionalism.…”
Section: Current Evidence Of the Benefits Of International Clinical E...mentioning
confidence: 99%